Transcriptomic rationale for synthetic lethality‐targeting ERCC1 and CDKN1A in chronic myelomonocytic leukaemia. (24th May 2018) - Hurtado, Ana M.; Luengo‐Gil, Gines; Chen‐Liang, Tzu H.; Amaral, Fabio; Batta, Kiran; Palomo, Laura; Lumbreras, Eva; Przychodzen, Bartlomiej; Caparros, Eva; Amigo, Marıa L.; Dıez‐Campelo, Maria; Zamora, Lurdes; et al.
Summary: Despite the absence of mutations in the DNA repair machinery in myeloid malignancies, the advent of high‐throughput sequencing and discovery of splicing and epigenetics defects in chronic myelomonocytic leukaemia (CMML) prompted us to revisit a pathogenic role for genes involved in DNA damage response. We screened for misregulated DNA repair genes by enhanced RNA‐sequencing on bone marrow from a discovery cohort of 27 CMML patients and 9 controls. We validated 4 differentially expressed candidates in CMML CD34 + bone marrow selected cells and in an independent cohort of 74 CMML patients, mutationally contextualized by targeted sequencing, and assessed their transcriptional behavior in 70 myelodysplastic syndrome, 66 acute myeloid leukaemia and 25 chronic myeloid leukaemia cases. We found BAP1 and PARP1 down‐regulation to be specific to CMML compared with other related disorders. Chromatin‐regulator mutated cases showed decreased BAP1 dosage. We validated a significant over‐expression of the double strand break‐fidelity genes CDKN1A and ERCC1, independent of promoter methylation and associated with chemorefractoriness. In addition, patients bearing mutations in the splicing component SRSF2 displayed numerous aberrant splicing events in DNA repair genes, with a quantitative predominance in the single strand break pathway. Our results highlight potential targets in this disease, which currently has few therapeutic options.